Strong-Form Efficiency with Monopolistic Insiders - Chau, Minh; Vayanos, Dimitri (Review of Financial Studies, 2008)
We study market efficiency in an infinite-horizon model with a monopolistic insider. The insider can trade with a competitive market maker and noise traders, and observes privately the expected growth rate of asset dividends. In the absence of the insider, this information would be reflected in prices only after a long series of dividend observations. The insider chooses, however, to reveal the information very quickly, within a time converging to zero as the market approaches continuous trading. Although the market converges to strong-form efficiency, the insider's profits do not converge to zero.